Health surveillance of workers previously exposed to asbestos in the experience of Occupational Medicine at the Pisa University Hospital, according to Tuscany Region guidelines - Guglielmi, Giovanni; Bonotti, Alessandra; Foddis, Rudy; Pistelli, Alessandra; Fallahi, Poupak; Cristaudo, Alfonso (La Medicina del Lavoro, 2018)
The Tuscany Region, according to Resolution 396/2016, offered workers residing in Tuscany and who were previously exposed to asbestos, a specific health surveillance program across the entire regional territory. The University Hospital of Pisa, as part of this program, plays a second level role in the health surveillance of asbestos workers, but directly follows a cohort of ex-exposed individuals (first level) in the occupational medicine care-service of the hospital as well. The aim of this study was to present the results of the health surveillance protocol for the exposed workers carried out by the Unit of Occupational Preventive Medicine. The health surveillance protocol consists essentially of health and work history, medical and instrumental examinations (i.e. performing pulmonary function and imaging tests), along with some experimental blood biomarkers such as Soluble Mesothelin-Related Peptides (SMRP) and osteopontin. The population currently followed by the Unit of Occupational Preventive Medicine of the University Hospital of Pisa consists of 1740 patients with an average age of 65.82 years (±9.51) and an average time duration of asbestos exposure of 17.63 years. 20.2% of subjects suffered from benign lung asbestos-related disease, while 36% of subjects were affected by benign lung disease unrelated to asbestos exposure. In 1.93%, a neoplastic disease related or possibly related to a professional asbestos exposure was diagnosed. Our experience outlined and supported the need for a specific follow-up health program for asbestos workers based on less invasive diagnostic examinations.